Monetary Transmission Mechanism in Central and Eastern Europe: Surveying the Surveyable - Égert, Balázs (OECD Economics Department Working Papers, 2008)
This paper surveys recent advances in empirical studies of the monetary transmission mechanism (MTM), with special attention to Central and Eastern Europe (CEE). Our results indicate that the strength of the exchange rate pass-through substantially declined over time mainly due to a fall in inflation rates and to some extent due to the so-called composition effect. The asset price channel is weak and is likely to remain weak because of shallow stock and private bond markets and because of low stock and bond holdings of domestic household. House prices may become an exception with higher levels mortgage lending and with high owner occupancy ratios. While the credit channel could be a powerful channel of monetary transmission - as new funds raised on capital markets are close to zero in CEE - it is actually not, as both commercial banks and non-financial corporations can escape domestic monetary conditions by borrowing from their foreign mother companies. The moderately good news is, however, that those banks and firms are influenced by monetary policy in the euro area because their parent institutions are themselves subjected to the credit channel in the euro area